FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENERAPAN METODE AMENOREA LAKTASI DI PUSKESMAS RASIMAH AHMAD - Febriniwati Rifdi; Martika Sari (Maternal Child Health Care, 2022)
Lactation Amenorrhoea Method (LAM) is one of the contraceptive methods recommended for breastfeeding mothers <6 months. The low coverage of the use of LAM is one of the challenges for health workers, including in the work area of the Rasimah Ahmad Health Center. This study aims to determine the factors related to the application of the Lactation Amenorrhoea Method (LAM) in breastfeeding mothers in the working area of Rasimah Ahmad Public Health Center in Bukittinggi in 2018. This type of research is descriptive analytic with a cross sectional study approach. This research was carried out in the work area of Rasimah Ahmad Public Health Center in July - August 2018 with a population of 169 people. Sampling using purposive sampling technique with a sample size of 63 people. Data collection used a research questionnaire, data analysis included univariate analysis and bivariate analysis using chi-square test. The results showed that 55.6% of respondents had low knowledge, 61.9% did not work, 52.4% had poor husband support, 50.8% were active officers, 58.7% were not LAM. There is a relationship between knowledge (p = 0.009 and OR = 4.889), employment status (p = 0.02, OR = 4.433), husband's support (p = 0.009, OR = 4.688) and the role of health workers (p = 0.028, OR = 3,696) with the application of LAM. It can be concluded that knowledge, employment status, husband's support and the role of health workers with the application of LAM. It is expected that all parties, especially the health workers, should always improve the socialization efforts to improve the knowledge of breastfeeding mothers about LAM so that they can apply the LAM method in a special family planning program for nursing mothers. MAL. Dapat disimpulkan bahwa pengetahuan, status pekerjaan, dukungan suami dan peran petugas kesehatan dengan penerapan MAL. Diharapkan kepada semua pihak terutama pihak petugas kesehatan untuk selalu meningkatkan upaya sosialisasi demi meningkatkan pengetahuan ibu menyusui tentang MAL sehingga dapat menerapkan metode MAL dalam ber-KB khusus untuk ibu menyusui.  Keywords: Breastfeeding mother, LAM